Application of the Latest CLSI EP Guidelines in light-initiated chemiluminescent assay for testosterone - Ai, liangai; Cao, Xiaojing; Ren, Xin-xin; Kang, lan; Zhang, Dan; Chang, Xin (Journal of Medical Biochemistry, 2025)
Background: A commercial light-initiated chemiluminescent assay (LiCA) for testosterone (T) measurement was developed. This study comprehensively evaluated the analytical performance of LiCA-T following the Clinical and Laboratory Standards Institute (CLSI) Evaluation Protocols (EP) series guidelines. Methods: From 1st July 2023, both the manufacturer and clinical end-users conducted rigorous performance evaluations in accordance with CLSI EP guidelines. Assessments included precision, linearity, accuracy/trueness, detection limits, and interference testing using collected clinical samples. Results: Manufacturer evaluations demonstrated excellent assay performance: repeatability (1.41-4.39%), intermediate imprecision (1.62-7.29%), and reproducibility (1.62-7.22%). The method showed linearity across 0.10-16.64 ng/mL (ADL=10%). Method comparison with MS reference yielded a limit of agreement (LoA) of -19.5% to 14.4%, with ≤10.00% bias at medical decision points. Sensitivity parameters included: LoB (0.041 ng/mL), LoD (0.049 ng/mL), and LoQ (0.060 ng/mL at 20% imprecision). The assay demonstrated robust interference resistance against hemoglobin (2 mg/mL), biotin (20 ng/mL), triglyceride (3 mg/mL), and bilirubin (0.157 mg/mL). All manufacturer claims were successfully verified by independent clinical end-user testing. Conclusion: The LiCA-T assay satisfies all performance criteria specified in CLSI latest EP guidelines (including EP06-Ed2 and EP07-Ed3), demonstrating reliable analytical performance across all critical validation parameters for clinical testosterone measurement.